Personalized monitoring of electrical remodelling during atrial fibrillation progression via remote transmissions from implantable devices. Issue 5 (16th December 2019) - Lillo-Castellano, José María; González-Ferrer, Juan José; Marina-Breysse, Manuel; Martínez-Ferrer, José Bautista; Pérez-Álvarez, Luisa; Alzueta, Javier; Martínez, Juan Gabriel; Rodríguez, Aníbal; Rodríguez-Pérez, Juan Carlos; Anguera, Ignasi; Viñolas, Xavier; García-Alberola, Arcadio; et al.
Abstract: Aims: Atrial electrical remodelling (AER) is a transitional period associated with the progression and long-term maintenance of atrial fibrillation (AF). We aimed to study the progression of AER in individual patients with implantable devices and AF episodes. Methods and results: Observational multicentre study (51 centres) including 4618 patients with implantable cardioverter-defibrillator +/−resynchronization therapy (ICD/CRT-D) and 352 patients (2 centres) with pacemakers (median follow-up: 3.4 years). Atrial activation rate (AAR) was quantified as the frequency of the dominant peak in the signal spectrum of AF episodes with atrial bipolar electrograms. Patients with complete progression of AER, from paroxysmal AF episodes to electrically remodelled persistent AF, were used to depict patient-specific AER slopes. A total of 34 712 AF tracings from 830 patients (87 with pacemakers) were suitable for the study. Complete progression of AER was documented in 216 patients (16 with pacemakers). Patients with persistent AF after completion of AER showed ∼30% faster AAR than patients with paroxysmal AF. The slope of AAR changes during AF progression revealed patient-specific patterns that correlated with the time-to-completion of AER ( R 2 = 0.85). Pacemaker patients were older than patients with ICD/CRT-Ds (78.3 vs. 67.2 year olds, respectively, P < 0.001) and had a shorter median time-to-completion of AER (24.9 vs. 93.5 days, respectively, P = 0.016). Remote transmissions in patients with ICD/CRT-D devices enabled the estimation of the time-to-completion of AER using the predicted slope of AAR changes from initiation to completion of electrical remodelling ( R 2 = 0.45). Conclusion: The AF progression shows patient-specific patterns of AER, which can be estimated using available remote-monitoring technology.